Answer:
x =
![(17)/(14)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5zdu662svsx2hscwxl24ybgulufnvpgcrd.png)
Explanation:
simplify both sides of the equation
-9x + 10 - 5x = - 7
-9x + 10 + - 5x = -7
(-9x + -5x) + (10) = -7 (combine like terms)
-14x + 10 = -7
subtract 10 from both sides
-14x + 10 - 10 = -7 - 10
-14x = -17
divide both sides by -14
=
![(-17)/(-14)](https://img.qammunity.org/2021/formulas/mathematics/college/2bagn9w5vm4uydzwu69f4xofq42bvqpyef.png)
x =
![(17)/(14)](https://img.qammunity.org/2021/formulas/mathematics/high-school/5zdu662svsx2hscwxl24ybgulufnvpgcrd.png)